Numerical Simulation of Mixed-Mode Fatigue Crack Growth for Compact Tension Shear Specimen - Yahya Ali Fageehi; Abdulnaser M. Alshoaibi (Advances in Materials Science and Engineering)
This work concentrates on the fracture behaviour of the compact tension specimen under mixed-mode loading, and numerical investigation using ANSYS Mechanical APDL 19.2 finite element program with different modes of mix angles is carried out. The prediction of mixed-mode fatigue life under constant amplitude fatigue loading for the compact tension shear specimen (CTS) is employed using Paris’ law model for two different loading angles with agreement to the experimental results. The predicted values of ΔKeq were compared with the experimental and analytical data for various models. Depending on the analysis, the findings of the present study show consistency with the results achieved with similar models of predicting the equivalent stress intensity factor. In addition, the direction of crack growth derived from the analysis was observed to follow the same trend of the literature experimental results.